2020
DOI: 10.2334/josnusd.19-0451
|View full text |Cite
|
Sign up to set email alerts
|

Morphological foundations of pain processing in dental pulp

Abstract: Dental pulp is densely innervated by sensory afferents that are primarily involved in nociception. Elucidating the type and properties of these afferents and their distribution patterns within the dental pulp is crucial for understanding the mechanisms of acute dental pain and dental hypersensitivity. Recent studies on the release of the transmitter glutamate and the expression of glutamate receptors and vesicular glutamate transporters (VGLUT) in the pulpal axons and trigeminal ganglion (TG) have suggested th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 75 publications
1
10
0
Order By: Relevance
“…The fraction of myelinated Piezo1+ axons of all Piezo1+ axons decreased significantly between the radicular pulp (55.9 ± 6.0%) and the peripheral pulp (2.0% ± 1.0%), whereas the fraction of unmyelinated Piezo1+ axons increased significantly from 44.1% ± 6.0 % in the radicular pulp to 98.0% ± 1.0% in the peripheral pulp ( Figure 4D ), suggesting that virtually all Piezo1+ myelinated axons in the radicular pulp lose their myelin and become unmyelinated at the peripheral pulp. This assumption can also be supported by a previous study, showing shedding of myelin sheath in myelinated axons in the rat dental pulp ( Figure 4E , modified from Bae and Yoshida, 2020 ).…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…The fraction of myelinated Piezo1+ axons of all Piezo1+ axons decreased significantly between the radicular pulp (55.9 ± 6.0%) and the peripheral pulp (2.0% ± 1.0%), whereas the fraction of unmyelinated Piezo1+ axons increased significantly from 44.1% ± 6.0 % in the radicular pulp to 98.0% ± 1.0% in the peripheral pulp ( Figure 4D ), suggesting that virtually all Piezo1+ myelinated axons in the radicular pulp lose their myelin and become unmyelinated at the peripheral pulp. This assumption can also be supported by a previous study, showing shedding of myelin sheath in myelinated axons in the rat dental pulp ( Figure 4E , modified from Bae and Yoshida, 2020 ).…”
Section: Resultssupporting
confidence: 85%
“… Electron micrographs showing immunostaining for Piezo1 (arrowheads) in myelinated (asterisks) and unmyelinated axons (arrows) in the radicular (A) , the core of the coronal (B) , and the peripheral (C) regions of the human dental pulp, and a histogram showing the fraction of Piezo1+ myelinated and unmyelinated axons of all Piezo1+ axons in each region of the human dental pulp (D) , and an electron micrograph of myelinated axon showing shedding of its myelin sheath during its course in the rat dental pulp [ (E) , modified from Bae and Yoshida, 2020 ]. Piezo1+ myelinated axons are more frequent in the radicular pulp than in the core of the coronal pulp, and virtually all Piezo1+ axons are unmyelinated in the peripheral pulp, suggesting that most Piezo1+ myelinated axons in the radicular pulp lose their myelin and become unmyelinated in the peripheral pulp.…”
Section: Resultsmentioning
confidence: 99%
“…21 Further studies have demonstrated that this increased fluid movement into the dentinal tubules excites both C-and Aδ-fibers in the dentin-pulp junction, which in turn activates the dental pain signaling pathway. 22,23 The expression of thermosensitive and mechanosensitive receptors, as well as voltage-gated ion channels involved in pain signaling in the primary dental afferent neurons, 19 further supports the hydrodynamic theory.…”
Section: Pathophysiology and Mechanisms Of Pain In Dentin Hypersensit...mentioning
confidence: 74%
“…This neural component of DP tissues remains relevant after development. In adult tissue, peripheral axons comprise 40% of DP volume (40), are the basis for pain processing (41), and participate in immune response (42,43). Although neurons cannot be isolated by the tissue digestion techniques applied in the present work, we were able to show that glial cells alone, myelinated and non-myelinated Schwann cells, comprise 12.39% of the DP cell population.…”
Section: Discussionmentioning
confidence: 99%